(3CZGfi aj GdehSjbis - (3GdJGOdj , EHQGgje Hf eMeO Hf YHO GdbGOQ GdMSfj GdWGdHj, CHh ESMGb,J (B1311 (3g` s ((3GdWjH Hf YeQ Hf GdWjH Hf CMeO GdQHGWi s)
(3ChdgG (B:s
(3hHYO ajbhd deG JYGWjJ Ref GdTHGH bQGA Ydhe GdQjGVI s
(3BNQgG (B:s
(3ceG CTGQ dPdc ai GdcJGH GdSGOS ef LeY GdLhGeY s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3HChdg agQSs
(3Hg fXGe GdJYbjHIs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdehSjbi hGdZfGAs